Beyond the nation-state: Anchoring supranational institutions in international business research - Hartmann, Simon; Lindner, Thomas; Müllner, Jakob; Puck, Jonas (Journal of International Business Studies, 2022)
In this paper, we broaden the conceptualization of institutions beyond the nation-state and develop the concept of an institutional triality that represents two national institutional environments and the supranational level. While much of international business (IB) research has focused on national institutions and the differences between them, little attention and theorizing has been dedicated to the supranational institutions that form an integral part of the global institutional ecosystem. First, we conduct an interdisciplinary bibliometric survey on supranational institutions and a qualitative review of the central publications. Second, we initiate theory building and conceptualize supranational institutions from an IB point of view, distinguish them from related IB concepts, and discuss the conceptual properties of supranational institutions that are most relevant for MNCs. Building on these distinctions and properties, we provide a conceptual framework for understanding supranational institutions in the institutional triality. Third, we provide avenues for IB research building on the delineations, the conceptual properties, and the conceptual framework. Supplementary Information: The online version contains supplementary material available at 10.1057/s41267-022-00537-3.